OPTIMIZATION OF SUBSURFACE DRIP LATERAL DEPTHS AND IRRIGATION LEVELS FOR BEST YIELD RESPONSE OF ONION (ALLIUM CEPA L.) - M. S. Afzal; M. J. M. Cheema; M. A. Shahid; M. Arshad; T. Khaliq (Journal of Animal and Plant Sciences, 2020)
Drip irrigation is being used for growing high value crops as an alternative to traditional flood irrigation. However, high installation cost and short life (due to exposure to atmosphere) are major hindrances in its adoptability. Sub Surface Drip Irrigation (SSDI) is getting popularity for high value crops, as drip lines buried in the soil. However, its efficiency for different crops is still needed to explore. For this purpose, a study was designed to grow onion (Allium cep L.) on raised beds and irrigated through surface and subsurface drip irrigation for two years (i.e. 2015-16 and 2016-17). Three irrigations based on 100%, 80% and 60% of crop water requirement were applied with the drip laterals buried at depths of 0, 6, 12, 18 and 24 cm with three replications for each treatment. Dripper discharge of 4 l/s with operating pressure of one kg cm-2 was maintained for each irrigation. A significant effect of lateral depth was observed with maximum yield of 13,990 kg ha-1 obtained at 12 cm lateral depth, while minimum yield of 9,020 kg ha-1 was observed at the lateral depth of 24 cm. It can be concluded that shallow depth vegetables like onion can be grown with maximum irrigation water use efficiency of 57 kg ha-1 mm-1 using SSDI buried at the depth of 12 cm. Therefore, it is recommended that onion should be grown under SSDI with 12 cm depth and irrigated with 80% of CWR for better crop production and higher drip application efficiency in semi-arid regions.
Keywords: SSDI; lateral depth; irrigation water use efficiency; yield characteristics